A security enhanced authentication and key distribution protocol for wireless networks - Lv, Chao (2013)
Authentication and key distribution (AKD) protocols become more and more important in the design of wireless networks. Especially, the communication efficiency and security are the critical factors. In this paper, we first analyse the vulnerabilities of an AKD protocol for wireless networks under three types of attacks. Then, we propose an enhanced AKD protocol to overcome those vulnerabilities with the security functionality to prevent those malicious attacks. Security analysis and formal verification mainly using Automated Validation of Internet Security Protocols and Applications toolkit show that the proposed protocol is secure against those attacks.